2011
DOI: 10.1002/mabi.201100277
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer‐Based Macromolecular Conjugate for the Kidney‐Directed Delivery of a Multitargeted Sunitinib Analogue

Abstract: The development of a macromolecular conjugate of a multitargeted tyrosine kinase inhibitor is described that can be used for renal-specific delivery into proximal tubular cells. A novel sunitinib analogue, that is, 17864, is conjugated to a NH(2) -PAMAM-G3 dendrimer via the platinum (II)-based Universal Linkage System (ULS™). The activity of 17864 is retained after coordination to the ULS linker alone or when coupled to NH(2) -PAMAM-G3. 17864-UlS-NH(2) -PAMAM-G3 is non-toxic to proximal tubular cells in vitro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…glutathione, which offers the possibility of stimulus-responsive drug release. Previously the Lx linker has been used for the attachment of various drug molecules to macromolecular carrier systems including antibodies [19,20] and polymers [21]. In these cases, the central platinum atom binds the functional moiety to the carrier molecule via coordination sites such as nitrogen and sulfur atoms with free electron pairs, while the other two coordination sites of platinum are made up permanently by an ethylenediamine bridge, which is a strong bidentate ligand that cannot be readily replaced by the mentioned monodentate ligands.…”
Section: Preparation Of Micellesmentioning
confidence: 99%
See 1 more Smart Citation
“…glutathione, which offers the possibility of stimulus-responsive drug release. Previously the Lx linker has been used for the attachment of various drug molecules to macromolecular carrier systems including antibodies [19,20] and polymers [21]. In these cases, the central platinum atom binds the functional moiety to the carrier molecule via coordination sites such as nitrogen and sulfur atoms with free electron pairs, while the other two coordination sites of platinum are made up permanently by an ethylenediamine bridge, which is a strong bidentate ligand that cannot be readily replaced by the mentioned monodentate ligands.…”
Section: Preparation Of Micellesmentioning
confidence: 99%
“…This led us to combine in this work these 2 promising concepts by designing PEG-P(HPMA) block copolymers with hydrophobic 4-(methylthio)benzoyl (MTB) side groups that can stabilize the micellar core via coordinative crosslinking. As crosslinker we used the metal-organic linker [ethylenediamineplatinum(II)] 2+ , herein called Lx, which is a coordinative linker molecule that has been used for the conjugation of drug molecules to a number of synthetic or natural carrier systems such as hyperbranched polymers and antibodies [19][20][21][22]. The properties of core-crosslinked micelles are presented and compared with those of uncrosslinked micelles.…”
Section: Introductionmentioning
confidence: 99%
“…The dendrimer can effectively deliver captopril to the kidney (Matsuura et al, 2018a) and thus reduce its side effects. PAMAM dendrimer-based macromolecular conjugate of a multitargeted sunitinib analog also showed proximal tubular cell-targeted delivery (Dolman et al, 2012b). The sunitinib analog is conjugated to NH(2)-PAMAM-G3 dendrimer with a platinumbased linker and displayed efficient accumulation in rodent kidneys.…”
Section: Dendrimersmentioning
confidence: 99%
“…They conjugated Sunitinib to the terminal amines of PAMAM-G3. They concluded that in vivo accumulation of this novel compound make it suitable as efficient dendrimer therapeutics for the treatment of renal disease (27).…”
Section: Dendrimersmentioning
confidence: 99%